Trans,trans-farnesol, an antimicrobial natural compound, improves glass ionomer cement properties. - Aline Rogéria Freire de Castilho; Pedro Luiz Rosalen; Isaac Jordão de Souza Araújo; Igor Lebedenco Kitagawa; Cecilia Atem Gonçalves de Araújo Costa; Malvin N Janal; Marcelo Corrêa Alves; Simone Duarte; Paulo Noronha Lisboa Filho; Rafael Nobrega Stipp; Regina Maria Puppin-Rontani (PLoS ONE, 2019)
A series of experiments were conducted to characterize a novel restorative material. We explored the effect on biological, physical and chemical properties of glass ionomer cement (GIC) adding-the naturally occurring tt-farnesol (900 mM). Two groups were accomplished for all assays: GIC+tt-farnesol and GIC (control). Biological assays: 1) agar diffusion against some cariogenic bacteria; 2) S. mutans biofilm formation and confocal laser scanning microscopy-CLSM. 3) gtfB, gtfC, gtfD, gbpB, vicR, and covR expression; 4) MTT and microscopic morphology. Physical properties assays: 1) roughness; 2) hardness; 3) compressive strength and 4) diametral tensile strength. Chemical assay: Raman spectroscopy. The adding of tt-farnesol to GIC led to larger zones of inhibition (p<0.05), biofilms with a short-term reduction in bacterial viability but similar biomass (p>0.05). Polysaccharides levels increased over time, similarly over groups (p>0.05). Viable and non-viable S. mutans were seen on the specimens' surface by CLSM but their virulence was not modulated by tt-farnesol. The tt-farnesol increased the HaCaT cell viability without impact on compressive and diametral tensile strength and roughness although the hardness was positively affected (p<0.05). Raman confirmed the presence of tt-farnesol. The incorporation of tt-farnesol into GIC inhibited the growth of cariogenic bacteria but had a little effect on the composition, structure and physiology of the biofilm matrices. Also, the tt-farnesol increased the hardness and the biocompatibility of the GIC, not influencing negatively other physical properties of the restorative material.